Impact analysis of environmental policies during business cycle : DSGE approach - Slezáková, Eva (2021)
In this thesis I analyse the impact of carbon pricing policy on the environmental, social and economic outcomes, using environmental dynamic stochastic general equilibrium model. In this model, negative externality arises from production process in form of greenhouse gas emissions, which in return pose damages on the economy and decrease productivity of its inputs. I extend the closed economy real business cycle model of Heutel (2012) for small open economy with international financial markets sector and estimate the effects that different levels of fixed carbon tax have on the economy. The model is calibrated to fit Slovak data. I find that the carbon tax increases volatility of environmental variables in response to productivity and country risk shocks. Pro-cyclical carbon tax would, therefore, help to internalize the negative environmental externality more efficiently. Additionally, I provide a social welfare analysis and calculate welfare gains from different carbon tax settings in comparison to the economy with no environmental policy in place. I find the welfare gains to be positive for every carbon tax level in both closed and open economy model, however the highest level of carbon tax leads to significantly smaller gains, than it is for lower tax settings. Also, the welfare gains from carbon policy implementation have shown to be marginally lower in small open economy.